(3aJM GdeJYGd aj eOM GdfYGd GdeTQaIs - (3GdebQj , CHh GdYHGS CMeO Hf eMeO Hf CMeO Hf jMji Hf YHO GdQMef GdebQj,J (B1041 (3g` s ((3CMeO CZG Hf jMji Hjc GdYbjdi s)
(3ChdgG (B:s
(3hHYO ajbhd CMeO Hf eMeO GdTgjQ HGdebhi GdeGdci GdeZQHi Ef gPG cJGH aJM GdeJYGdi VefJg hUa GdfYGd hbO SCdJ Gddg Cf jchf ef NjQ GdaYGd s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JMQjQg HThGd ef YGe KdGKjf hGda HGdbGgQI GdeYRjI GdeMQhSI GdN ehGVY jSjQg eQQJ HYO gPG GdJGQjN hCdMbJ HYV EdMGbGJ bGd gPG hcJHg eDdag GdabjQ CMeO Hf eMeO GdebQi hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjg JbQjXGJ dHYV GdYdeGA BNQgG dJGL GdOjf CMeO Hf EHQGgje GdeGdci Gdeci NGOe GdYde GdTQja HGdeSLO GdMQGe (B_ (3HgG eWGdH ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs